UJI COBA PENEBANGAN KAYU BERBASIS ZERO WASTE DAN RAMAH LINGKUNGAN PADA HUTAN ALAM DI PROVINSI KALIMANTAN TENGAH - Soenarno; Dulsalam; Yuniawati (BRIN Publishing, 2020)
Over the last five years (2013−2017) there has been a deficit of ± 23.2 million m3year of wood raw materials,while the facts in the field of timber harvesting are still wasteful with leaving logging waste reaching an average of 17%of the annual production quota target of 9.1 million m3/year. The trial of zero waste-based and environmentallytimber harvesting method (ZWL) is important to strengthen the tree length logging methods. This research aimed toobtain data and technical information related to the efficiency of wood utilization and the potential of timber loggingwaste. The trial results showed that zero waste and environmentally timber harvesting methods could improve woodutilization efficiency by 9%, from an average of 82.9% to an average of 91.9%, and reduce the potential for clearbole (BBC) logging waste from an average of 12% (0.863 m3/ tree) to only 8.1% (0.418 m3/tree). In addition, itwas able to save the potential of logging waste from stems above the branch (BAC) ranging from 2.8−11.2% with anaverage of 6.4% (0.418 m3/tree). However, ecologically it could not reduce damage to residual stands which reached37.7% while conventional methods amounted to 38.8%. Potential logging waste both BBC and BAC were mostlydefective (50.5−58.3%), and some were still good (14.4−26.3%) while those with broken conditions were still quitehigh (22.6-27.3% ). Until now, the potency of timber harvesting waste has not been utilized due to the considerationof the high cost of Non-Tax Government Income (PNBP) levies, uncertainty in the application of the Minister ofEnvironment and Forestry Regulation Number: P.1/Menlhk/Setjen/Kum.1/1/2019, and the ZWL method hasnot been informed yet to minimize the cost of logging waste extraction. In order to reduce timber harvesting waste andresidual stand damage, the forest management refresh logging and skidding techniques to improve the skills of thechainsaw and the tractor operators.